Potential of Combined Curcuma zedoaria and Piper crocatum Leaf Extracts as Natural Male Antifertility Agents: an Experimental Study in Mice - Sukarjati; Mitha Novia Sari (Postgraduate, University of Mataram, 2025)
Curcuma zedoaria and Piper crocatum are indigenous Indonesian herbal plants containing various bioactive compounds. C. zedoaria is known to contain curcumin, tannins, saponins, and flavonoids, while P. crocatum contains piperine, tannins, saponins, flavonoids, alkaloids, and triterpenoids. This study aimed to investigate the effects of white turmeric extract, red betel leaf extract, and their combination on the spermatogenic cells of male mice. Extracts were obtained using the maceration method. A total of 30 male mice, aged 3 months and weighing 25–30 grams, were randomly divided into four treatment groups with three replications each: control, white turmeric extract, red betel extract, and a combination of both extracts. The extracts were administered orally at doses of 50, 100, and 150 mg/kg BW for individual extracts, and 25:25, 50:50, and 75:75 mg/kg BW for the combined treatment, over 35 days. Histological sections of the testis were prepared following standard laboratory protocols. One-way ANOVA showed a significant decrease (p < 0.05) in all cell types in treated groups, with the most substantial reduction observed at the 75:75 mg/kg BW combination dose. The conclusion of this study is that the combined extract of C. zedoaria and P. crocatum has the potential as an antifertility